2008
DOI: 10.1007/s10886-007-9413-z
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Amylase Induction by Tannin-Enriched Diets as a Possible Countermeasure Against Tannins

Abstract: Tannins are characterized by protein-binding affinity. They have astringent/bitter properties that act as deterrents, affecting diet selection. Two groups of salivary proteins, proline-rich proteins and histatins, are effective precipitators of tannin, decreasing levels of available tannins. The possibility of other salivary proteins having a co-adjuvant role on host defense mechanisms against tannins is unknown. In this work, we characterized and compared the protein profile of mice whole saliva from animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 65 publications
4
69
0
Order By: Relevance
“…However, in the animals of the 5.0% groups, there were no significant changes of the parotid glands except for hypertrophy. Parotid gland hypertrophy similar to the one observed in the present study was reported in mice orally treated with 5.0% tannic acid, known as a bitter component, for ten days (da Costa et al, 2008). In the clinical observation, clear salivation could not be observed in the treated animals.…”
Section: Discussionsupporting
confidence: 86%
“…However, in the animals of the 5.0% groups, there were no significant changes of the parotid glands except for hypertrophy. Parotid gland hypertrophy similar to the one observed in the present study was reported in mice orally treated with 5.0% tannic acid, known as a bitter component, for ten days (da Costa et al, 2008). In the clinical observation, clear salivation could not be observed in the treated animals.…”
Section: Discussionsupporting
confidence: 86%
“…Tannins, and polyphenolic compounds more generally, can act as ubiquitous, nonspecific inhibitors of digestion enzymes and glucose transporters (Manzano and Williamson 2010;Mimsek et al 2014), thereby reducing the rate of digestion and absorption of key nutrients, particularly glucose (Zucker 1983). Tanninrich food has been shown to affect the activity of salivary amylase in some animals by increasing it in some cases (Ahmed et al 1991;Da Costa et al 2008;Lamy et al 2010), although the inverse has been observed in cockerels (Ahmed et al 1991).…”
Section: Salivary Amylasesmentioning
confidence: 99%
“…For feeding experiments, GSE or tannic acid was mixed well with the powdered basal diet, CRF-1 (Oriental Yeast Co., Tokyo, Japan), at a concentration of 0% (control) or 5.0%. The dosage of GSE and tannic acid was determined based on results from the previous subchronic toxicity study and published report (da Costa et al 2008), respectively. For gavage experiments, the dose of GSE corresponded to 5.0% in the feeding experiment as calculated from the food consumption volume measured once a week in the feeding experiment.…”
Section: Gse (Exgrapementioning
confidence: 99%
“…Based on the fact that one a-amylase isoform was overexpressed in the saliva of mice treated with tannin-enriched diets which also induced parotid gland hypertrophy (Da costa et al 2008), indicated that GSE might induce the same a-amylase isoform as tannin-enriched diets only in the parotid gland, not in the other salivary glands. After the recovery period, a slight focal basophilic change in the parotid glands was observed in some of the animals in all of 6.-Ultrastructure of the glandular epithelial cells of parotid glands from rats treated with GSE or tannic acid by feeding for 4 weeks.…”
mentioning
confidence: 99%